Industrial internet of things and cyber-physical systems transforming the conventional to digital - Kumar, Pardeep; Ponnusamy, Vasaki 1974-; Jain, Vishal (IGI Global, 2020)
"This book explores recent advances in the development, implementation, and business impact of IoT technologies on sustainable societal development and improved life quality"--
Keywords: Internet of things / Industrial applications; Cooperating objects (Computer systems)